Slow Deep Breathing dan Alternate Nostril Breathing terhadap Penurunan Tekanan Darah pada Pasien Hipertensi - Faradilla Miftah Suranata; Agung Waluyo; Wati Jumaiyah; Dhea Natashia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to determine the effectiveness of slow deep breathing and alternate nostril breathing on reducing blood pressure in patients with hypertension. This study uses a quasi-experimental design with a pretest-posttest group design approach. Friedman test results showed that there were differences in systolic blood pressure (x2 = 34.09; p <0.001) and diastolic (x2 = 28.74; p <0.001) in the slow deep breathing intervention group. Based on the post hoc test, measurements from time to time obtained p values ​​(p = 0.001) for both systolic and diastolic blood pressure. Meanwhile there were differences in blood pressure in the alternate nostril systolic breathing group (x2 = 15.50; p <0.001), diastolic (x2 = 17.18; p <0.001). Post hoc test found a significant decrease in systolic and diastolic blood pressure from each measurement time during the intervention period with p values ​​0.005 and 0.025, respectively. Conclusion, in this study that slow deep breathing is much more effective in reducing blood pressure in hypertensive patients. Keywords: Alternate Nostril Breathing, Hypertension, Decreased Blood Pressure, Slow Deep Breathing